2020
DOI: 10.1038/s41598-020-65717-3
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal loss of the insulin receptor in osteoprogenitor cells does not impart a metabolic phenotype

Abstract: The relationship between osteoblast-specific insulin signaling, osteocalcin activation and glucometabolic homeostasis has proven to be complex and potentially inconsistent across animal-model systems and in humans. Moreover, the impact of postnatally acquired, osteoblast-specific insulin deficiency on the pancreas-to-skeleton-to-pancreas circuit has not been studied. To explore this relationship, we created a model of postnatal elimination of insulin signaling in osteoprogenitors. Osteoprogenitor-selective abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…We cannot comment on the protein's effect when given exogenously, since we did not inject osteocalcin into mice in our study. However, we [1], and others [5][6][7], found no evidence that supports an endogenous hormonal role for osteocalcin. Should Dr. Karsenty make available batches of his biologically-active osteocalcin without restriction, interested parties could avoid the potential confounder of reagent quality [8] and assess objectively whether osteocalcin has a hormonal role when administered exogenously.…”
contrasting
confidence: 79%
“…We cannot comment on the protein's effect when given exogenously, since we did not inject osteocalcin into mice in our study. However, we [1], and others [5][6][7], found no evidence that supports an endogenous hormonal role for osteocalcin. Should Dr. Karsenty make available batches of his biologically-active osteocalcin without restriction, interested parties could avoid the potential confounder of reagent quality [8] and assess objectively whether osteocalcin has a hormonal role when administered exogenously.…”
contrasting
confidence: 79%
“…Furthermore, it was found that insulin signaling in murine osteoblasts enhanced the conversion of osteocalcin into the active, undercarboxylated form and regulated glucose homeostasis by signaling through GPRC6A in mice [34][35][36]. However, in another study, no signi cant changes were observed between mice with postnatal deletion of the insulin receptor in osteoprogenitor cells and control mice, although undercarboxylated osteocalcin levels were signi cantly decreased in the mutant mice [37]. Therefore, more studies are needed to clarify the molecular mechanism of action and functions of osteocalcin.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable controversy has arisen over several ndings that mouse models may not satisfactorily represent the human osteocalcin physiology [38]. The reasons for the variable metabolic phenotypes in terms of glucose and energy metabolism in different mouse models remain unclear [37]. However, the involvement of serum osteocalcin in MetS has been largely studied through cross-sectional research in humans [10,11,24,25,[39][40][41], which showed that serum osteocalcin levels were negatively associated with MetS.…”
Section: Discussionmentioning
confidence: 99%